An extraordinary cause for deep venous thrombosis. (10th February 2011) - Droog, W; van Beek, A J; Kooijman, R
Abstract : The authors present a case of a congenital absence of the infrarenal inferior vena cava in an 18-year-old man showing symptoms of deep venous thrombosis of the left leg. The congenital absence of the inferior vena cava is typically asymptomatic and is commonly reported as a fortuitous finding. Abnormalities of the inferior vena cava are risk factors contributing to the development of deep venous thrombosis. The absence of vena cava is underestimated in patients with deep venous thrombosis because in some cases compression B-mode ultrasonography will not reveal the condition. CT should be made available for all young patients with idiopathic deep venous thrombosis.